2017
DOI: 10.3892/ol.2017.7491
|View full text |Cite
|
Sign up to set email alerts
|

Mitogen-activated protein kinase signaling pathway in oral cancer (Review)

Abstract: Abstract. The mitogen-activated protein kinase (MAPK) signaling pathway is associated with tumor cell proliferation, differentiation, apoptosis, angiogenesis, invasion and metastasis. The present review assesses the involvement of the MAPK signaling pathway in oral cancer progression and invasion based on analysis of individual sub-pathways and their mechanisms of action. The regulation of this pathway for targeted oral cancer therapy is explored and the challenges confronting this, as well as corresponding po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
70
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(72 citation statements)
references
References 80 publications
1
70
0
1
Order By: Relevance
“…MAPK pathway is known to play a role in promoting cell proliferation, inhibiting apoptosis, promoting tumor angiogenesis and inducing invasion and metastasis in oral cancer. 30 We have previously observed marked overexpression and activation of MAPK1 in OKF6/ TERT1 cells chronically exposed to cigarette smoke. 12 Despite distinct genomic anomalies in OKF6/TERT1 cells chronically treated with cigarette smoke and shisha extract, interferon-signaling cascade was a commonly affected pathway in both models.…”
Section: Discussionmentioning
confidence: 91%
“…MAPK pathway is known to play a role in promoting cell proliferation, inhibiting apoptosis, promoting tumor angiogenesis and inducing invasion and metastasis in oral cancer. 30 We have previously observed marked overexpression and activation of MAPK1 in OKF6/ TERT1 cells chronically exposed to cigarette smoke. 12 Despite distinct genomic anomalies in OKF6/TERT1 cells chronically treated with cigarette smoke and shisha extract, interferon-signaling cascade was a commonly affected pathway in both models.…”
Section: Discussionmentioning
confidence: 91%
“…This feature was nicely described in a recent review [56]. This activity is mainly linked to its antioxidant effect, its capacity to decrease proliferative growth, the arrest of the cell cycle, and its proapoptotic properties [100][101][102][103][104][105][106]. In the last period, further studies have tried to increase the set of information related to mechanism of action, using esophagus, breast, bronchial epithelial, NSLC (non-small cell lung cancer), and colon cancer cell lines.…”
Section: Apigeninmentioning
confidence: 87%
“…Oxidative stress, mitochondrial dysfunction, accumulation of intracellular lipid derivatives, and in ammation (via IL-6 and TNFα) contribute to decreased activation of signaling molecules including PI3K and AKT leading to insulin resistance [45][46][47].The absence of sphingomyelin, a second messenger functions in a variety of cellular signaling pathways, leads to a shortened lifespan in animals and it suggests that sphingolipid signaling may play a role in neuronal function and animal stress response during aging [48]. The focal adhesion, mitogen-activated protein kinase (MAPK) signaling pathway and ErbB signaling pathway is module that is involved in cell proliferation, differentiation and migration [49][50][51].Focal adhesion, a signaling molecule associated with cell survival, relies on the interaction between integrins and actin to connect cells to the extracellular matrix [50]. Studies have shown that extracellular matrix proteins-cell interactions gives rise to target organ damage, and in ammatory pathways leading to calci cation or atherosclerosis [1,52].…”
Section: Discussionmentioning
confidence: 99%